Experimental Study on Detection of Deterioration in Concrete Using Infrared Thermography Technique - Jungwon Huh; Quang Huy Tran; Jong-Han Lee; DongYeob Han; Jin-Hee Ahn; Solomon Yim (Advances in Materials Science and Engineering)
Concrete is certainly prone to internal deteriorations or defects during the construction and operating periods. Compared with other nondestructive techniques, infrared thermography can easily detect the subsurface delamination in a very short period of time, but accurately identifying its size and depth in concrete is a very challenging task. In this study, experimental testing was carried out on a concrete specimen having internal delaminations of various sizes and at varying depths. Delaminations at 1 and 2 cm deep showed a good temperature contrast after only 5-minute heating, but delaminations at 3 cm practically identified the value of the temperature contrast from heating of 15 minutes. In addition, the size of the delamination at 3 cm deep could be estimated with a difference of 10% to 28% for 20 minutes of heating. The depth of the delamination was linearly correlated with the increase in its size.